1999
DOI: 10.1520/jfs14451j
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Illicit Cocaine Seizure Classification by Pattern Recognition Techniques Applied to Metal Data

Abstract: Fifteen metallic species, silver (Ag), aluminum (Al), calcium (Ca), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), potassium (K), magnesium (Mg), manganese (Mn), sodium (Na), nickel (Ni), lead (Pb), strontium (Sr) and zinc (Zn), were determined in 46 cocaine samples confiscated by the Spanish police in Galicia (northwest Spain). Classification of these cocaine samples according to their geographic origin (Colombia and Venezuela) was achieved by the application of pattern recognition techniques to the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 25 publications
1
39
0
8
Order By: Relevance
“…Nitric acid has been used by several authors [27][28][29] because the analytes are mobilized from the solid particles to the liquid media, which improves the precision of the method 7 , while nitrates do not interfere in the atomization paths for the metals involved. The concentrations selected, 2.0 mol L -1 for Cu, Fe and Zn and 4.0 mol L -1 for Mn, were used according to previous studies shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric acid has been used by several authors [27][28][29] because the analytes are mobilized from the solid particles to the liquid media, which improves the precision of the method 7 , while nitrates do not interfere in the atomization paths for the metals involved. The concentrations selected, 2.0 mol L -1 for Cu, Fe and Zn and 4.0 mol L -1 for Mn, were used according to previous studies shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, a number of factors must be considered to obtain an analytical performance comparable to that achieved with liquid sampling. The introduction of the sample as a slurry is an alternative that has been used to analyze a diversity of elements in different matrices [3][4][5][6][7][8] . Comprehensive reviews on this methodology have been reported in the literature 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…After separation of samples for preparation of samples for quantitative analysis, wet digestion method was used [9]. The 20 mg portion of the weighed sample was shaken up in a Chinese capsule with 2 ml of nitric acid (35% v/v) with a glass rod until complete digestion, and then the contents of the Chinese capsule were transferred to a 50 ml balloon and distilled water was added to the volume.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
“…Drug overdose is one of the major causes of mortality from poisoning in our country [9][10][11][12]. Deaths from acute drug poisoning are important in many aspects of medicine, in particular forensic medicine.…”
Section: Introductionmentioning
confidence: 99%
“…A comparação dos corretores Zeeman e D 2 para a compensação do BG na determinação de arsênio em água do mar por GFAAS, utilizando Pd(NO 3 ) 2 como modificador químico, demonstra essa eficácia. 12 Resultados exatos só foram obtidos com corretor Zeeman, que corrigiu efetivamente o BG causado por cloreto, sódio, potássio, cálcio e silício. Esse corretor também é o único capaz de corrigir BG estruturado, tal como aquele causado por fosfato sobre a determinação de Cd e Pb em baixos comprimentos de onda de absorção.…”
Section: Espectrometria Atômica Espectrometria De Absorção Atômicaunclassified